1997
DOI: 10.1577/1548-8640(1997)059<0303:uofdio>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Formalin during Incubation of Eyed Eggs of Inland Fall Chinook Salmon

Abstract: The influence of daily formalin treatments on eyed egg and fry mortality was evaluated during the incubation of eyed eggs of inland fall chinook salmon Oncorhynchus tshawytscha. A 3–5% increase in survival was observed in trays of eggs treated with formalin at 1,667 mg/L for 15 min daily from egg eye‐up until just before hatch compared with incubation trays from which dead eggs were manually removed to control Saprolegnia. Egg survival in trays receiving both daily formalin treatments and manual egg removal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
1
22
3
Order By: Relevance
“…Although this mortality is probably due to a number of factors, bacteria isolated during egg incubation have been implicated in these deaths in several studies (Barnes et al 1997(Barnes et al , 2005Stephenson et al 2003). Other researchers have also suggested that bacteria may negatively impact egg survival (Sauter et al 1987;Barker et al 1989;Holcomb et al 2005), although this relationship is far from certain (Barker et al 1990;Omnes et al 1993).…”
mentioning
confidence: 99%
“…Although this mortality is probably due to a number of factors, bacteria isolated during egg incubation have been implicated in these deaths in several studies (Barnes et al 1997(Barnes et al , 2005Stephenson et al 2003). Other researchers have also suggested that bacteria may negatively impact egg survival (Sauter et al 1987;Barker et al 1989;Holcomb et al 2005), although this relationship is far from certain (Barker et al 1990;Omnes et al 1993).…”
mentioning
confidence: 99%
“…After 396 temperature units of incubation, 20 aliquots of 15 eggs each from a common egg pool were transferred to 20, 9.5-cm diameter Petri dishes (300 eggs total) containing hatchery well water (total hardness as CaCO 3 , 360 mg/L; alkalinity as CaCO 3 , 210 mg/L; pH, 7.6; total dissolved solids, 390 mg/L) and incubated at 11°C using the technique described by Barnes and Durben [3].…”
Section: Methodsmentioning
confidence: 99%
“…This is of particular interest in South Dakota, where there is a high possibility of zebra mussel introduction into Lake Oahe, a reservoir containing a unique population of landlocked fall Chinook salmon (Oncorhynchus tshawytscha). This population is maintained entirely by spawning feral fish from the reservoir and then transporting the eggs to offreservoir hatcheries [3]. Thus, the objective of this study was to evaluate established treatments commonly used to prevent the spread of zebra mussels during fish transportation on salmonid egg survival.…”
Section: Introductionmentioning
confidence: 99%
“…Well water (11°C; 360 mg/L total hardness as CaCO 3 ; 210 mg/L alkalinity as CaCO 3 ; 390 mg/L dissolved solids; 7.6 pH) supplied both incubator types. Flows were set at 12 L/min, which was the minimum required for slight rolling of the eggs in the jars, and are the same flows typically used during landlocked fall Chinook salmon egg incubation in trays [5,13]. Eggs were inventoried by water displacement [1] prior to placement into the incubation units.…”
Section: All Experimentation Occurred At Mcnenny State Fishmentioning
confidence: 99%
“…Vertically-stacked trays have the advantage in that they use minimal floor space, require relatively small amounts of water, and allow for the handling of individual trays without disturbing the entire stack [1][2][3]. However, regular treatments of formalin or hydrogen peroxide must be used to control fungus (water molds) until at least the eyed-egg stage [1,4], and are recommended for use until hatch during tray incubation of landlocked fall Chinook salmon Oncorhynchus tshawytscha eggs [5]. While formalin is the most suitable chemical for fungal control, its use poses serious risks to human health [6,7], and techniques to minimize or eliminate formalin use in aquaculture are extremely desirable.…”
Section: Introductionmentioning
confidence: 99%